PENCATATAN AKUNTANSI YANG ADA DI DALAM BUKU TEKS AKUNTANSI SAAT INI - Ignatius Bondan Suratno; Bambang Purnomo; Benedicta Budiningsih (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
This study aims to describe the circumstances of the accounting record that already exists in the current accounting textbooks, benefit from accounting recording for the preparation of annual reports and taxes, and the recording of the more easily understood for students. This research is a descriptive study conducted at Sanata Dharma University in June-August 2017.The findings in this study is that accounting records that already exist in accounting textbooks are currently located in a condition where the recording of accounting cases as presented in the questionnaire is done when the parties involved make the record as a Taxpayer Agency that does not implement tax obligations, or not as an Individual Taxpayer, and or not as a taxable employers with an average score of 75%.Accounting records that provide more benefit for the preparation of annual reports and taxes are in a condition where the recording ofaccounting cases as presented in the questionnaire is done when the parties involved make the record as a Taxpayer Agency that perform taxation obligations, as an Individual Taxpayer, and as a Taxable Entrepreneur with an average score of 83%, the recording of the more easily understood for students when studying accounting materials integrated with tax instruments with an average score of 73%.Keywords: accounting, taxes, textbooks